Method and system for improving erosion resistance of laser cladding cobalt-based alloy coating
By performing stress annealing treatment after laser clad cobalt-based alloy coating, the problems of cracks and defects in the coating are solved, and the corrosion resistance and service life of the coating are significantly improved.
Patent Information
- Application Number
- CN202510095500.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-21
- Publication Date
- 2025-04-18
AI Technical Summary
The prior art is prone to cracks and defects in the laser clad cobalt-based alloy coating process, resulting in insufficient corrosion resistance of the coating and affecting the overall performance and service life of small-sized components.
By performing stress annealing treatment on the cobalt-based alloy coating after laser cladding, appropriate annealing process parameters are selected to reduce the occurrence of cracks and defects, ensuring the close bond between the coating and the substrate and excellent mechanical properties.
It significantly improves the corrosion resistance of cobalt-based alloy coating, reduces the generation of cracks and defects, enhances the bonding strength between the coating and the substrate, and extends the service life of small-sized components.
Smart Images

Figure CN119843274A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to but is not limited to the technical field of dissimilar metal welding, and in particular relates to a method and a system for improving the erosion resistance of a laser cladding cobalt-based alloy coating. Background Art
[0002] As a complex and sophisticated whole, the efficient and stable operation of a mechanical system depends on the coordinated work and good condition of each component. Among these components, some small-sized components such as piston rods need to work in extreme environments such as high temperature, high humidity, and strong corrosion. Their surfaces are often prone to wear and erosion, which affects the performance of the mechanical system. Therefore, improving the physical properties of such small-sized components, that is, their wear resistance and corrosion resistance, has become the key to ensuring the stable operation of the mechanical system. In order to improve the wear resistance and erosion resistance of such small-sized components, the industry has explored and practiced a variety of surface repair and strengthening methods. Traditional methods such as manual surfacing and tungsten carbide coating flame spraying can repair and strengthen the surface to a certain extent, but these methods have many limitations. When these methods are used to repair and strengthen components, the prepared coating has a large heat-affected zone, large deformation, and limited bonding strength with the substrate; therefore, it is difficult to achieve the ideal repair and strengthening effect. In addition, these traditional methods have problems such as high labor intensity and harsh on-site environment, which limit their practical application.
[0003] Laser cladding technology is an advanced surface modification technology that uses a high-energy-density laser beam as a heat source to melt the cladding material of a specific composition and quickly solidify it on the surface of the base material to form a cladding layer that is metallurgically bonded to the base material. This technology can significantly improve the wear resistance, corrosion resistance, and high-temperature resistance of the base material surface, and is widely used in the repair and strengthening of key components in the fields of aerospace, automobile manufacturing, energy and electricity, and petrochemicals. With its unique advantages, laser cladding technology overcomes the limitations of traditional alloy surface repair and strengthening methods and provides a new solution for the surface repair and strengthening of small-sized components.
[0004] Among many cladding materials, cobalt-based alloys occupy an important position in the field of metal surface strengthening due to their unique performance characteristics. This cemented carbide not only has excellent wear resistance and corrosion resistance, but also can maintain high strength in extreme high temperature environments, showing good resistance to thermal fatigue, thermal corrosion and wear. These characteristics make cobalt-based alloys an ideal choice for the preparation of corrosion-resistant and wear-resistant coatings, especially for small-sized components that need to maintain high performance under harsh working conditions. However, despite the many advantages of cobalt-based alloys, there are some technical challenges when using laser cladding technology to strengthen the key parts of complex small-sized components.
[0005] The laser cladding process involves the interaction between the high-energy-density laser beam and the base material and cladding material. Due to the significant differences in heating rates and heat dissipation conditions in various regions of complex components, the temperature gradient is large, heat accumulation is obvious, and thermal stress is concentrated during the cladding process. The phase composition of cobalt-based alloys is WC, Cr 7 C 3 During the laser cladding process, due to the difference in the solidification characteristics and thermal expansion coefficient of these carbides and the surrounding Co matrix, thermal stress is generated at the solidification interface. Under the continuous action of thermal stress, these carbides and the Co matrix gradually peel off, generating micropores. As the thermal stress continues to accumulate during the cladding process, micropores continue to germinate and expand, and adjacent micropores are connected in series with each other, gradually forming microcracks, which continue to expand and eventually form macroscopic cracks visible to the naked eye. This uneven heating and cooling process causes cracks inside the cobalt-based alloy cladding layer, which not only seriously damages the integrity and quality of the cladding layer, reduces the erosion resistance of the cladding layer, but also may further affect the overall performance and service life of complex components such as small-sized components. In addition, the physical properties of the cobalt-based alloy itself also increase the difficulty of laser cladding. Cobalt-based alloys usually have higher hardness and lower plasticity, which makes it difficult for the cladding layer material to release internal stress through plastic deformation during laser cladding, thereby increasing the risk of cracks. Especially when preparing large-scale or multi-pass or multi-layer cladding layers, as the thickness of the cladding layer increases, the cumulative effect of internal stress becomes more significant and the crack problem becomes more prominent.
[0006] Therefore, how to effectively control the generation of cracks during the laser cladding process has become the key to improving the quality of the cobalt-based alloy cladding layer and the performance of complex components. However, the current technology for repairing and strengthening the surface of small-sized components is generally traditional methods such as manual surfacing and tungsten carbide coating flame spraying. There are large heat-affected zones, large deformations, and limited bonding strength with the substrate, making it difficult to achieve ideal repair and strengthening effects. In the process of preparing cobalt-based alloy cladding layers using laser cladding technology, cracks are prone to occur due to the influence of heating rate and heat dissipation conditions, which not only affects the quality and erosion performance of the cladding layer, but may also have an adverse effect on the performance of small-sized components and reduce their service life.
[0007] In view of the above analysis, the technical problems that need to be solved urgently in the prior art are:
[0008] (1) How to effectively enhance the wear and erosion resistance of small-sized components;
[0009] (2) How to effectively reduce defects and cracks during the laser cladding process of cobalt-based alloys to ensure the quality of the cladding layer and the overall performance of the component. Summary of the invention
[0010] In view of the problems existing in the prior art, the present invention provides a method and system for improving the erosion resistance of laser cladding cobalt-based alloy coatings; so as to achieve "defect-free" cladding of cobalt-based alloy protective coatings, ensure the integrity and stability of the cladding layer structure and significantly improve the erosion resistance and service life of small-sized components. The laser cladding technology for preparing defect-free cobalt-based alloy cladding layers can effectively avoid cracks in the cladding layer by performing stress relief annealing on the cladding layer and selecting appropriate annealing process parameters.
[0011] The present invention is achieved by a method for improving the erosion resistance of a laser cladding cobalt-based alloy coating, comprising the following steps:
[0012] Step 1, performing surface pretreatment on the base material;
[0013] Step 2, preparing a cobalt-based alloy cladding layer by laser cladding technology;
[0014] Step three, the material after cladding is subjected to stress relief annealing treatment.
[0015] Furthermore, in the step 1, the surface of the base material is firstly processed by mechanical polishing to obtain a smooth and flat surface so as to enhance the bonding strength between the layer and the base material.
[0016] Furthermore, the base material is 1Cr11Ni2W2MoV martensitic stainless steel piston rod.
[0017] Furthermore, in step 2, a cobalt-based alloy cladding layer is prepared by laser cladding technology, and the process parameters of laser cladding of cobalt-based alloy are set as follows: laser power is 3KW, scanning speed is 20mm / s, spot diameter is 4mm, overlap rate is 70%, and powder amount is 10g / min.
[0018] Furthermore, the cladding layer material is Stellite 6 alloy powder with a particle size of 75 to 150 μm.
[0019] Furthermore, in the step three, the clad parts are annealed at a temperature of 650° C. After the annealing is completed, the samples are kept in a heat treatment furnace for 2 hours and cooled along with the furnace.
[0020] Another object of the present invention is to provide a method for improving the erosion resistance of a laser cladding cobalt-based alloy coating and a system for improving the erosion resistance of a laser cladding cobalt-based alloy coating, comprising:
[0021] A surface pretreatment module, used for performing surface pretreatment on the base material;
[0022] Cobalt-based alloy cladding layer preparation module, used to prepare cobalt-based alloy cladding layer by laser cladding technology;
[0023] The stress relief annealing treatment module is used to perform stress relief annealing on the material after cladding.
[0024] In combination with the above technical solutions and the technical problems solved, the advantages and positive effects of the technical solutions to be protected by the present invention are as follows:
[0025] First, the present invention effectively reduces the generation of micro cracks and defects in the cobalt-based alloy cladding layer by performing the key step of annealing after laser cladding of the cobalt-based alloy, thereby preparing a coating that is tightly bonded to the substrate, has excellent mechanical properties, and has significantly improved erosion resistance. It solves the problems of large heat-affected zones, large deformations, and limited bonding strength with the substrate that occur in the current technology for repairing and strengthening the surface of small-sized components, making it difficult to achieve ideal repair and strengthening effects. At the same time, the present invention also proposes an effective solution to the problem that cracks are easily generated during the laser cladding of cobalt-based alloys due to improper heating rate and heat dissipation conditions, significantly improving the quality and reliability of the cladding layer.
[0026] This invention not only provides a valuable theoretical basis and practical guidance for the optimization of laser cladding process, but also opens up a new path for surface strengthening and durability improvement of more complex parts. This technological innovation is of great significance for promoting the high-quality development of the manufacturing industry, especially in improving the service life and performance of key components.
[0027] Second, through the method of the present invention, the erosion resistance of the laser cladding cobalt-based alloy coating can be significantly improved, and the service life of parts can be effectively extended. This is particularly critical for mechanical equipment operating in high temperature, high humidity and highly corrosive environments, and can reduce the downtime rate of equipment operation. In addition, the high performance of the coating reduces the frequency of parts replacement, thereby significantly reducing the maintenance costs of the enterprise and improving economic benefits. The technology of the present invention can produce products with longer life and better performance, which has significant advantages in market competition. The present invention also expands the application scope of laser cladding technology, which is suitable for a variety of scenarios from small-sized parts to large-scale equipment, provides a comprehensive solution for material surface strengthening, and has high commercial value and industrial promotion prospects.
[0028] Traditional technologies have problems such as large heat-affected zone, severe deformation, and insufficient bonding strength when dealing with surface strengthening of small-sized components, and have never been able to achieve an ideal solution. The present invention combines optimized laser cladding process and stress relief annealing treatment to successfully reduce cracks and defects in the cladding layer, improve the bonding strength between the cladding layer and the substrate, and significantly improve the erosion resistance, filling the technical gap in the field of strengthening small-sized components at home and abroad.
[0029] The problem of surface strengthening of small-sized components: When processing small-sized components, traditional surfacing and spraying technologies have problems of deformation and insufficient bonding strength caused by high heat input. The present invention successfully prepares a cobalt-based alloy coating that is tightly bonded to the substrate and has excellent performance through high-precision laser cladding technology combined with reasonable annealing treatment, solving the long-standing technical problem of surface strengthening of small-sized components.
[0030] Laser cladding crack problem: During the laser cladding process, cracks are easily generated due to rapid cooling, which affects the coating quality. The present invention effectively eliminates residual stress, reduces cracks and other defects through stress relief annealing, and ensures the integrity and stability of the cladding layer.
[0031] Improved erosion resistance of cobalt-based alloy coatings: When used in complex environments, cobalt-based alloy coatings often face the problem of insufficient erosion resistance. The present invention significantly improves the erosion resistance of the coating, extends the life of components, and meets the application requirements under extreme working conditions.
[0032] The present invention provides a new method combining laser cladding and annealing processes, which optimizes the entire process from coating preparation to post-processing, significantly improving the performance of cobalt-based alloy coatings. Through technological innovation, it has led the development direction of the surface strengthening field, promoted the upgrading and progress of related industries, and helped high-performance equipment to operate reliably in extreme environments.
[0033] Third, in the prior art, due to the roughness of the substrate surface or the presence of pollutants, the bonding strength between the cobalt-based alloy cladding layer and the substrate material is insufficient, which easily leads to peeling or shedding of the coating. The present invention pre-treats the substrate surface finely by mechanical polishing, significantly improves the metallurgical bonding quality between the substrate and the cladding layer, effectively solves the problem of insufficient coating adhesion, and lays a foundation for improving the erosion resistance of the coating.
[0034] Traditional cladding methods easily lead to defects such as pores and cracks in the microstructure of the cladding layer, affecting the erosion resistance and service life of the coating. The present invention adopts optimized laser cladding process parameters (such as laser power, scanning speed, powder amount, etc.) to ensure the high density and composition uniformity of the cladding layer, and significantly improve the erosion resistance of the coating in complex environments.
[0035] During the laser cladding process, due to rapid heating and cooling, large thermal stress is easily generated in the cladding layer, resulting in crack generation or expansion. The present invention eliminates residual stress and optimizes the grain structure of the coating by performing stress relief annealing after cladding, significantly reducing the risk of crack formation and improving the stability and reliability of the coating.
[0036] In the prior art, the long-term stability of cobalt-based alloy coatings in high-erosion and high-wear environments is poor, which limits their application in key equipment. The present invention improves the hardness, toughness and corrosion resistance of the coating through systematic coating preparation and heat treatment process optimization, prolongs the service life of the equipment, and meets the high performance requirements in industrial applications.
[0037] Through the above innovative process, the present invention achieves a significant improvement in the erosion resistance of the cobalt-based alloy coating, solves the bottleneck problems of traditional technology in terms of adhesion, density, stress control and long-term stability of the cladding layer, and has broad industrial application prospects and economic value. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a flow chart of a method for improving the erosion resistance of a laser cladding cobalt-based alloy coating provided by an embodiment of the present invention;
[0039] Figure 2 1Cr11Ni2W2MoV steel sample and dimension diagram provided in the embodiment of the present invention;
[0040] Figure 3 This is a system structure diagram for improving the erosion resistance of laser cladding cobalt-based alloy coatings provided by an embodiment of the present invention;
[0041] Figure 4 The macroscopic morphology of the laser cladding cobalt-based alloy coating provided by the embodiment of the present invention; (a) surface morphology; (b) cross-sectional morphology;
[0042] Figure 5 This is a macroscopic morphology of a cobalt-based alloy coating provided by an embodiment of the present invention after stress relief annealing after laser cladding; (a) surface morphology; (b) cross-sectional morphology;
[0043] Figure 6 1 is a microscopic morphology of a laser cladding cobalt-based alloy coating provided in an embodiment of the present invention; (a) without stress relief annealing; (b) after stress relief annealing;
[0044] Figure 7 1 is a transmission electron microscope photograph of stacking faults and twins in the laser cladding cobalt-based alloy coating provided by an embodiment of the present invention; (a) stacking faults; (b) twins;
[0045] Figure 8 The corrosion morphology of the laser cladding Stellite 6 alloy cladding layer provided in the embodiment of the present invention is as follows; (a) 100 μm stress-free annealing sample; (b) 10 μm stress-free annealing sample; (c) 100 μm stress-relief annealing sample; (d) 10 μm stress-relief annealing sample. DETAILED DESCRIPTION
[0046] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0047] Example 1
[0048] 1. Surface pretreatment of substrate materials
[0049] 1Cr11Ni2W2MoV martensitic stainless steel bars with a size of Φ19mm*85mm were selected as the substrate material. The substrate surface was mechanically polished using 80-grit sandpaper to remove the oxide layer, contaminants and rough areas on the surface to obtain a smooth and flat substrate surface.
[0050] 2. Preparation of Co-based Alloy Cladding Layer
[0051] The polished substrate was fixed on the workbench of the laser cladding equipment, and Stellite 6 alloy powder (particle size 75-150μm) was used as the cladding material. The laser cladding process parameters were set as follows: laser power 2.5kW, scanning speed 20mm / s, spot diameter 4mm, overlap rate 70%, powder amount 10g / min. A cobalt-based alloy coating with a thickness of 2mm was formed by laser cladding.
[0052] 3. Annealing after cladding
[0053] The prepared coating sample was placed in a heat treatment furnace, kept at 600°C for 2 hours, and then cooled in the furnace. After annealing, the residual stress between the coating and the substrate was effectively released, and the microstructure was more uniform.
[0054] The prepared coating has a dense microstructure and a hardness exceeding 455HV, which significantly improves the erosion resistance of the sample.
[0055] Example 2
[0056] 1. Surface pretreatment of substrate materials
[0057] 19mm×85mm 1Cr11Ni2W2MoV martensitic stainless steel bars were selected as the base material. The base surface was mechanically polished in turn using sandpaper with a grinding particle size of 80 mesh and 120 mesh. After completion, the base surface was cleaned with alcohol to remove oil and impurities to ensure a clean surface.
[0058] 2. Preparation of Co-based Alloy Cladding Layer
[0059] The cobalt-based alloy cladding material (Stellite 6 alloy powder, particle size 75-150μm) was uniformly covered on the substrate surface using laser cladding equipment. The laser cladding parameters were set as follows: laser power of 3.0kW, scanning speed of 20mm / s, spot diameter of 4mm, overlap rate of 70%, and powder supply of 10g / min. A uniform coating with a thickness of about 4mm was formed during the cladding process. To ensure the uniformity and quality of the coating, the scanning path was optimized during the cladding process to avoid local over-melting or under-melting.
[0060] 3. Heat treatment after cladding
[0061] The clad samples were placed in a vacuum heat treatment furnace for stress relief annealing. The annealing parameters were: the temperature was set at 650°C, the holding time was 2 hours, and the temperature was slowly cooled to room temperature in the furnace. The heat treatment process effectively reduced the internal stress in the cladding layer, improved the microstructure, and improved the durability of the coating.
[0062] 4. Performance Testing
[0063] After testing, the cladding coating has a hardness of about 520HV, the number of microcracks has been significantly reduced, and the erosion resistance has been improved by about 40% compared with the untreated sample. The coating has shown good wear resistance and adhesion under simulated high impact load conditions, proving that the process is suitable for harsh working conditions in actual applications.
[0064] In this embodiment, the cladding parameters and heat treatment process are optimized, and the effect of the improved process is demonstrated under different power and heat treatment conditions compared with embodiment 1. This is in line with actual operation and can also expand the protection scope of the patent's technical solution.
[0065] like Figure 1 As shown, an embodiment of the present invention provides a method for improving the erosion resistance of a laser cladding cobalt-based alloy coating, comprising the following steps:
[0066] Step 1, performing surface pretreatment on the base material;
[0067] Step 2, preparing a cobalt-based alloy cladding layer by laser cladding technology;
[0068] Step three, the material after cladding is subjected to stress relief annealing treatment.
[0069] The material used in the embodiment of the present invention is a 1Cr11Ni2W2MoV martensitic stainless steel piston rod as the base material. Figure 2 Schematic diagram of the sample. The cladding layer material is Stellite 6 alloy powder with a particle size of 75 to 150 μm.
[0070] In the step 1, the surface of the base material is firstly processed by mechanical polishing to obtain a smooth and flat surface so as to enhance the bonding strength between the layer and the base material.
[0071] In the step 2, a cobalt-based alloy cladding layer is prepared by using laser cladding technology, and the process parameters of laser cladding of cobalt-based alloy are set as follows: laser power is 3KW, scanning speed is 20mm / s, spot diameter is 4mm, overlap rate is 70%, and powder amount is 10g / min.
[0072] In the step three, the clad parts are annealed at a temperature of 650° C. After the annealing is completed, the samples are kept in a heat treatment furnace for 2 hours and cooled along with the furnace.
[0073] The present invention provides a method for improving the erosion resistance of a cobalt-based alloy coating by combining laser cladding technology with a heat treatment process. The working principle is described in detail below from the three main steps of substrate pretreatment, cladding layer preparation, and annealing treatment.
[0074] The base material is 1Cr11Ni2W2MoV martensitic stainless steel piston rod. In order to enhance the bonding strength between the cladding layer and the base material, the base surface is mechanically polished. Mechanical polishing can remove the surface oxide layer, pollutants and rough areas to obtain a smooth and flat surface, thereby ensuring a stronger metallurgical bond between the cobalt-based alloy cladding layer and the base during the cladding process. In addition, polishing can also reduce the generation of interface defects during the cladding process, significantly improving the adhesion and erosion resistance of the cladding layer.
[0075] The cobalt-based alloy cladding layer was prepared on the substrate surface using laser cladding technology. Stellite 6 alloy powder (particle size 75-150μm) was selected as the cladding material, and the laser cladding process parameters were set as laser power 3KW, scanning speed 20mm / s, spot diameter 4mm, overlap rate 70%, and powder amount 10g / min. These parameters have been precisely optimized to ensure that the cladding layer has a dense microstructure and uniform composition distribution. During the laser cladding process, the high-energy laser beam quickly melts and solidifies the alloy powder and the substrate surface to form a metallurgical bonding layer with high hardness and corrosion resistance. The uniformity and density of the cladding layer are key factors in improving erosion resistance.
[0076] After the cladding is completed, the material is subjected to stress relief annealing. The annealing temperature is set at 650°C, and the sample is kept in the heat treatment furnace for 2 hours and then cooled with the furnace. The main function of the annealing treatment is to eliminate the thermal stress generated during the laser cladding process, reduce the residual stress inside the cladding layer and the substrate, and improve the microstructure of the cladding layer. Through annealing, the microcracks and grain boundary defects that may exist in the cladding layer are alleviated or repaired, further enhancing the toughness and erosion resistance of the cladding layer.
[0077] After the above three steps, the prepared cobalt-based alloy cladding layer has high hardness, high strength and excellent corrosion resistance. The dense metallurgical bonding layer formed during the laser cladding process provides excellent erosion resistance, while the annealing process further optimizes the microstructure of the material and reduces the possibility of stress concentration and crack propagation. Through scientific process control, this method significantly improves the erosion resistance of the piston rod under complex working conditions and extends its service life.
[0078] In summary, the present invention effectively solves the problem of insufficient erosion resistance of cobalt-based alloy coatings through the organic combination of mechanical polishing, laser cladding and annealing treatment, and is suitable for industrial scenarios with high wear resistance and erosion resistance, such as petroleum, chemical industry, marine engineering and other fields.
[0079] like Figure 3 As shown, an embodiment of the present invention provides a method for improving the erosion resistance of a laser cladding cobalt-based alloy coating and a system for improving the erosion resistance of a laser cladding cobalt-based alloy coating, comprising:
[0080] A surface pretreatment module, used for performing surface pretreatment on the base material;
[0081] Cobalt-based alloy cladding layer preparation module, used to prepare cobalt-based alloy cladding layer by laser cladding technology;
[0082] The stress relief annealing treatment module is used to perform stress relief annealing on the material after cladding.
[0083] The system for improving the erosion resistance of a laser cladding cobalt-based alloy coating provided in an embodiment of the present invention significantly improves the erosion resistance and service life of the coating through the synergistic effect of surface pretreatment, cladding layer preparation and stress relief annealing treatment.
[0084] The first step, surface pretreatment module
[0085] The surface pretreatment module is used to treat the base material to ensure the bonding strength between the coating and the base. The oxide layer, impurities and rough areas on the surface of the base material are removed by mechanical polishing to make the surface smooth and reduce the generation of interface defects during the coating preparation process. After pretreatment, the surface of the base material obtains better metallurgical bonding conditions, laying the foundation for the subsequent cladding layer preparation.
[0086] Step 2: Cobalt-based alloy cladding layer preparation module
[0087] This module uses laser cladding technology to prepare cobalt-based alloy cladding layers. During the laser cladding process, a high-energy laser beam instantly melts the cobalt-based alloy powder (such as Stellite 6) and the substrate surface and quickly solidifies it to form a dense and uniform metallurgical bonding layer. The module is equipped with a precise process control system that can optimize parameters such as laser power, scanning speed, spot diameter, and powder amount to ensure the uniformity of the coating composition and the density of the microstructure, thereby improving the wear resistance and corrosion resistance of the coating.
[0088] The third step is stress relief annealing treatment module
[0089] After the cladding is completed, the material may have large residual stress, resulting in cracks or defects. The stress relief annealing treatment module releases the internal stress of the material and optimizes the grain structure of the coating by heating the clad material to a specific temperature (such as 650°C) and keeping it warm for a period of time (such as 2 hours). After annealing, the toughness and crack resistance of the coating are significantly improved, while the overall erosion resistance is enhanced.
[0090] Step 4: System Synergy
[0091] This system solves the problems of insufficient coating adhesion, crack generation and poor erosion resistance in the traditional laser cladding process through the coordinated work of three modules: surface pretreatment, cladding layer preparation and stress relief annealing. The surface pretreatment module ensures the bonding strength of the coating, the cladding layer preparation module forms a dense coating structure, and the stress relief annealing module further optimizes the coating performance. The overall system is suitable for coating reinforcement of key components in high temperature, high humidity and strong corrosion environments, providing a reliable anti-erosion protection solution for mechanical systems.
[0092] The embodiments of the present invention significantly improve the performance of the cobalt-based alloy coating through modular design and precise process control, and have broad industrial application prospects and significant technical advantages.
[0093] The specific application fields or related products of the present invention.
[0094] Aerospace: Due to the excellent wear resistance, corrosion resistance and high temperature resistance of the cobalt-based alloy coating, the present invention can be widely used in the repair and strengthening of key parts in the aerospace field.
[0095] Petrochemical industry: Some mechanical equipment in these industries are subject to extreme working conditions such as high temperature, high pressure, and strong corrosion. The technology of the present invention can effectively improve the reliability and durability of the equipment.
[0096] Relevant evidence of the technical effects achieved by the embodiments of the present invention.
[0097] In the embodiment of the present invention, the material obtained after stress relief annealing is subjected to macroscopic morphology observation, microscopic morphology characterization and impact corrosion test. The specific test steps are as follows:
[0098] (1) In the process of preparing metallographic samples, the sample surface is polished with sandpaper of increasing mesh size, and after polishing, a mirror-like sample surface is obtained. The microstructure of the cladding layer is characterized by an optical microscope;
[0099] (2) In the preparation of transmission samples, the coating samples were ground to a thickness of 50 μm and punched into discs with a diameter of 3 mm. Then, in an electrolytic double-spray device, a double-spray solution consisting of 10% perchloric acid and 90% alcohol was used at a voltage of 30 V and a temperature of -20°C to obtain a thin area suitable for TEM observation. The microstructure of the cladding layer was observed using a transmission electron microscope.
[0100] (3) The sample was cut into 15.0 mm × 10.0 mm × 2.0 mm samples using a wire cutting machine. The substrate and the cladding layer were subjected to erosion tests using a full-function erosion test machine. The cladding layer was placed in the middle of the nozzle of the erosion equipment. The nozzle diameter was 2 mm. Sedimentation water was used as the fluid. The sand-water ratio was 1:10. The composition of the sand was SiO 2 The deposition water temperature was 25 °C and the erosion pressure was 7 MPa to simulate the erosion environment of the sample. After the erosion test, the erosion morphology was observed using a scanning electron microscope.
[0101] The data obtained from the test were analyzed to determine the degree of influence of the present invention on the performance of the cobalt-based alloy coating and small-sized components: the influence of the present invention on the performance of the cobalt-based alloy coating and the base material was analyzed in combination with the sample microstructure, microstructure and erosion test results.
[0102] Cobalt-based alloys are prepared using laser cladding technology. In order to address the problem that the erosion resistance of cobalt-based alloy coatings prepared on small-sized components is poor, stress relief annealing of the cladding layer can effectively reduce the generation of cracks and defects in the cobalt-based alloy cladding layer, thereby preparing a coating that is tightly bonded to the substrate, has excellent mechanical properties, and significantly improved erosion resistance, which significantly improves component performance and extends its service life.
[0103] For the samples that were not subjected to stress relief annealing after laser cladding, large-sized cracks can be seen on the entire multi-channel coating surface, e.g. Figure 4 As shown in (a) of the figure. The sample was cut and its cross section was observed. It was found that the cracks not only existed on the surface of the coating, but also penetrated the entire cladding layer, forming multiple cracks, such as Figure 4As shown in (b). This is caused by the large difference between the composition of the cladding layer and the composition of the substrate. After the cladding raw material is melted by the heat injected by the laser, the difference in composition makes the melting and cooling rates uneven, resulting in stress inside the molten pool, thereby causing cracks; in addition, the cobalt-based coating has a higher hardness and is also prone to cracks when fused with a lower hardness substrate. Such a cracked cobalt-based alloy coating cannot effectively enhance the surface wear resistance of the component, and because the integrity of the coating is destroyed, it also becomes a channel for the penetration of corrosive media and wear particles. In a corrosive environment, these cracks will accelerate the corrosion reaction, making the substrate under the coating more susceptible to corrosion, resulting in the peeling of the coating and damage to the substrate, thereby losing the strengthening effect on the substrate, seriously reducing the service life and safety of the component.
[0104] For the samples that were subjected to stress relief annealing after laser cladding, the macroscopic morphology of the coating surface was observed. The coating surface showed uniform structural characteristics, and no cracks or other macroscopic defects that may affect the coating performance were found, such as Figure 5 In order to further verify the internal structure and integrity of the coating, the sample was cut and its cross section was observed. It was found that a tight and strong metallurgical bond was formed between the coating and the substrate material, without any peeling or delamination. The internal structure of the coating was intact and without cracks, as shown in Figure 1. Figure 5 As shown in (b). During the laser cladding process, due to rapid heating and cooling, large residual stress will be generated inside the cladding layer. The stress relief annealing treatment effectively eliminates these residual stresses, balances the internal stress state of the coating, and obtains a coating with uniform structure and good wear and erosion resistance, thereby effectively improving the performance of the component.
[0105] The microstructure of the cladding layer was further observed using a transmission electron microscope. The cladding layer consisted of two different phases. Since the carbon content of the Stellite 6 alloy was 1.22%, the network-distributed hard carbides were wrapped around the cobalt-based solid solution. It was a hypoeutectic alloy. In the samples that had not been subjected to stress annealing, the transmission electron microscope images clearly showed a large number of cracks and holes around the cobalt-based solid solution, such as Figure 6 As shown in (a) in the figure. These defects not only destroy the integrity of the cladding layer, but also may become stress concentration areas, which may cause more serious structural damage during subsequent use. However, after the stress relief annealing treatment, the carbides and the cobalt matrix are well bonded, and no obvious cracks appear, as shown in the figure. Figure 6 As shown in (b), the annealing treatment not only effectively releases the residual stress in the cladding layer, but also improves the bonding state between the carbide and the cobalt matrix, thereby significantly improving the overall strength of the cladding layer.
[0106] Through TEM analysis, it was observed that twins existed in the Co-based alloy cladding layer, such as Figure 7 As shown. Due to the low stacking fault energy of cobalt-based alloys, dislocations are easily decomposed. A large number of dislocations are continuously generated and decomposed under the influence of various external factors. These decomposed dislocations further interact with each other to form dislocation entanglements, which effectively hinder the slip and climb of dislocations inside the crystal. Secondly, twins divide the originally larger grains into multiple small pieces. This segmentation not only changes the stress distribution state inside the grains, but also limits the free path of dislocations inside the crystal to a certain extent, which has a positive effect on preventing cracking and improving the performance of cobalt-based alloy cladding layers.
[0107] The corrosion resistance morphology of Stellite 6 alloy cladding layer is as follows: Figure 8 As shown in Figure 2. In the erosion process of the cladding layer containing cracks in the unannealed state, the structure around the original cracks first falls off, and deep grooves are formed around the cracks ( Figure 8 a and Figure 8 b). By observing the erosion morphology of the crack-free cladding layer after stress relief annealing, the erosion surface roughness of the annealed Stellite 6 alloy cladding layer is lower than that of the substrate and cracked cladding layer. The dents and micro-cutting marks are finer, and the non-directional overlapping distribution of the extrusion lip is not as obvious as that of the substrate. There is no obvious large tissue shedding on the surface of the cladding layer, and the hard phase particles effectively resist tissue shedding.
[0108] After the Stellite 6 alloy coating was laser clad on the surface of 1Cr11Ni2W2MoV, its erosion resistance was greatly improved, which was mainly determined by the crystal structure of the Stellite 6 cobalt-based alloy. The cobalt was cooled to room temperature under equilibrium solidification conditions to obtain a stable hexagonal close-packed ε-Co structure. Due to the extremely fast cooling rate, the Stellite 6 alloy coating prepared by laser cladding finally obtained a metastable γ-Co with a face-centered cubic structure. Under the continuous action of external forces such as high-pressure water and fine sand particles, the easily deformable face-centered cubic structure γ-Co will be transformed into a stable close-packed hexagonal structure ε-Co before the metal material leaves the surface. This stable hexagonal crystal structure of Co is prone to twinning, so this phase change can not only absorb and dissipate a large amount of high-pressure water impact energy, but also enable the twins in Co to divide the grains into several small pieces, which limits the freedom of dislocations to a certain extent, and thus has a strengthening effect on the matrix. Therefore, the Stellite 6 alloy coating can withstand large impact forces without causing large deformation on the surface of the material. In addition, in the Stellite 6 cobalt-based alloy coating, carbides are well bonded to the γ-Co matrix. Therefore, laser cladding of Stellite 6 cobalt-based alloy on the surface of 1Cr11Ni2W2MoV substrate can greatly improve its erosion resistance.
[0109] It should be noted that the embodiments of the present invention can be implemented by hardware, software, or a combination of software and hardware. The hardware part can be implemented using dedicated logic; the software part can be stored in a memory and executed by an appropriate instruction execution system, such as a microprocessor or dedicated design hardware. It can be understood by a person of ordinary skill in the art that the above-mentioned devices and methods can be implemented using computer executable instructions and / or contained in a processor control code, such as a carrier medium such as a disk, CD or DVD-ROM, a programmable memory such as a read-only memory (firmware), or a data carrier such as an optical or electronic signal carrier. Such code is provided on the carrier medium. The device and its modules of the present invention can be implemented by hardware circuits such as very large-scale integrated circuits or gate arrays, semiconductors such as logic chips, transistors, etc., or programmable hardware devices such as field programmable gate arrays, programmable logic devices, etc., can also be implemented by software executed by various types of processors, and can also be implemented by a combination of the above-mentioned hardware circuits and software, such as firmware.
[0110] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modification, equivalent substitution and improvement made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.
Claims
1. A method for improving the erosion resistance of laser cladding cobalt-based alloy coating, characterized in that: The following steps are involved: Step 1: mechanically polishing the surface of the stainless steel substrate to remove the surface oxide layer, pollutants and rough areas; Step 2: using laser cladding technology to prepare a cobalt-based alloy cladding layer on the polished substrate surface, wherein the laser cladding process parameters include that the cladding material is Stellite 6 alloy powder with a particle size of 75 to 150 μm; Step three, placing the prepared cladding layer material in a heat treatment furnace for stress relief annealing treatment, the annealing temperature is 650° C., the heat preservation time is 2 hours, and then cooling with the furnace.
2. The method for improving the erosion resistance of the laser cladding cobalt-based alloy coating according to claim 1, characterized in that: In the step 1, the surface of the base material is firstly processed by mechanical polishing to obtain a smooth and flat surface so as to enhance the bonding strength between the layer and the base material.
3. The method for improving the erosion resistance of laser cladding cobalt-based alloy coating according to claim 2, characterized in that: The base material is 1Cr11Ni2W2MoV martensitic stainless steel piston rod.
4. The method for improving the erosion resistance of laser cladding cobalt-based alloy coating according to claim 1, characterized in that: In the step 2, a cobalt-based alloy cladding layer is prepared by using laser cladding technology, and the process parameters of laser cladding of cobalt-based alloy are set as follows: laser power is 3KW, scanning speed is 20mm / s, spot diameter is 4mm, overlap rate is 70%, and powder amount is 10g / min.
5. The method for improving the erosion resistance of laser cladding cobalt-based alloy coating according to claim 4, characterized in that: The cladding layer material is Stellite 6 alloy powder with a particle size of 75 to 150 μm.
6. The method for improving the erosion resistance of laser cladding cobalt-based alloy coating according to claim 1, characterized in that: In the step three, the clad parts are annealed at a temperature of 650° C. After the annealing is completed, the samples are kept in a heat treatment furnace for 2 hours and cooled along with the furnace.
7. A system for improving the erosion resistance of laser cladding cobalt-based alloy coatings according to any one of claims 1 to 6, characterized in that: include: A surface pretreatment module, used for performing surface pretreatment on the base material; The cobalt-based alloy cladding layer preparation module is used to prepare the cobalt-based alloy cladding layer by laser cladding technology; the stress relief annealing treatment module is used to perform stress relief annealing treatment on the material after cladding.
Citation Information
Patent Citations
Method for laser cladding Co-based alloy coating at blast-furnace tuyere
CN101519704A
Method for cladding alloy on surface of metallic matrix
CN102115882A
Tool Coating Processing Method
US20220243314A1
Turbine blades and methods for depositing an erosion resistant coating on the same
WO2006094935A1
Cited By
Additive manufacturing gradient alloy and preparation method thereof
CN120158746A